When communities pull their weight: The economic costs of an integrated agriculture and nutrition home-grown preschool meal intervention in Malawi - Margolies, Amy; Gelli, Aulo; Daryanani, Roshan; Twalibu, Aisha; Levin, Carol (SAGE Publications, 2021)
Background: Community-based preschool meals can provide an effective platform for implementing integrated agriculture and nutrition programs. However, there is little evidence on the costs and cost-efficiency of implementing these types of multisectoral interventions.